2002
DOI: 10.1093/bja/aef252
|View full text |Cite
|
Sign up to set email alerts
|

Posture used by anaesthetists during laryngoscopy

Abstract: Novice anaesthetists should be given explicit instructions on correct trolley height and should be taught to intubate with a straight back.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…[ 4 ] To facilitate glottic visualisation, anaesthesiologists often adopt various postures such as flexing the neck, bending forward, stooping, bending their knees, standing on their toes or exerting their arms. [ 5 ] Although these positions are held for short periods during laryngoscopy and intubation, repeated performance in these stressful positions may have long-term impacts on joint performance. [ 6 ] Therefore, it is crucial to consider ergonomics and adopt proper techniques to minimise the risk of long-term injury from the performer's standpoint and ensure optimal patient care.…”
Section: Discussionmentioning
confidence: 99%
“…[ 4 ] To facilitate glottic visualisation, anaesthesiologists often adopt various postures such as flexing the neck, bending forward, stooping, bending their knees, standing on their toes or exerting their arms. [ 5 ] Although these positions are held for short periods during laryngoscopy and intubation, repeated performance in these stressful positions may have long-term impacts on joint performance. [ 6 ] Therefore, it is crucial to consider ergonomics and adopt proper techniques to minimise the risk of long-term injury from the performer's standpoint and ensure optimal patient care.…”
Section: Discussionmentioning
confidence: 99%
“…The trajectories of vertical head movement and head tilting in novices correspond to our previous study using ML 8) . Other authors demonstrated that novices who used ML were crouching and getting their faces close to the face of the mannequin during tracheal intubation 2,[5][6][7] . Therefore, lowering the head by bending the body and bringing the face closer to the face of the patient by turning the face more downward is a typical posture for novices during tracheal intubation, regardless of the type of laryngoscope.…”
Section: Discussionmentioning
confidence: 99%
“…Whitten stated in her textbook that novices crouch and take the wrong posture with their head close to the mouth of patients during tracheal intubation 2) . Several authors have shown that the posture during tracheal intubation using ML in simulation settings differs between the novices and experts, and novices tend to lean their back and neck more forward and head closer to the mouth [3][4][5][6][7] . Our previous study using motion capture and eye-tracking systems in the simulation setting also showed that the novices who used ML lowered their heads more, turned their faces more downwards, and their eyes turned upward during tracheal intubation 8) .…”
Section: Introductionmentioning
confidence: 99%